Fractured families--united countries?: family, nostalgia and nationbuilding in Das Wunder von Bern and Goodbye Lenin! - Uecker, Matthias (Intellect, 2007)
The article compares the role and construction of nostalgia in two of the most successful German films released in 2003, Das Wunder von Bern and Goodbye Lenin!. While both films portray a close connection between male adolescence, incomplete families, and nostalgia for a simpler past, Goodbye Lenin! exposes this view of the GDR as an artificial and largely fictional construction, whereas Das Wunder von Bern attempts to create a sense of authenticity for its nostalgic recreation of 1950s West Germany. Despite this significant difference, both films are shown to pursue a common ideological project: their narratives are focused on a nostalgic farewell to the past in order to develop a positive attitude to the future of a re-unified Germany. To this purpose, both films’ central characters and their families are presented as representative, allegorical embodiments of German culture whose development in the course of the narrative functions as a model for the audience.